Effects of Adding Insoluble Non-starch Polysaccharides and Exogenous Enzymes to a Commercial Broiler Diet on the Growth Performance and Carcass Weight of Broiler Chickens - Hartini, S.; Purwaningsih, P. (Pakistan Journal of Nutrition, 2017)
Background and Objective: It is possible that a commercial broiler ration that contains many fleas/insects and excess fine feed may have poor nutrient quality. This study aimed to investigate the effects of Wheat Pollard (WP), Rice Hull (RH), phytase and cellulase supplementation in a commercial broiler diet on the growth performance, carcass weight and gut characteristics of broiler chickens from 0-35 days of age. Methodology: A total of 175 male broiler chicks of 1 day old (Lohmann) were fed using 7 dietary treatments (5 replicates treatment–1). The diets used were as follows: (1) A commercial broiler diet as a control (C) diet, (2) C+WP (CWP)+phytase, (3) CWP+cellulase, (4) CWP+phytase+cellulase, (5) C+RH (CRH)+phytase, (6) CRH+cellulase and (7) CRH+phytase+cellulase. Wheat pollard and RHs were added at 40 g kg–1 of diet. Phytase was added at 1250 FTU kg–1 and cellulase was added at 250 U kg–1. Results: The control diet contained a low level of Ca (0.5%) and total P (0.4%). Treatment diets did not affect the growth performance of broiler chickens (p>0.05). Birds fed diets 5, 6 and 7 exhibited higher carcass weights (p<0.05), the lightest duodenum and jejunum weights (p<0.01), the lowest jejunum pH values (p<0.05) and the lowest cecal pH values (p<0.01), as well as higher cecal acetic and butyric acid concentrations (p<0.01). The duodenal digesta was the highest in birds fed the control diet (p<0.05). Conclusion: Adding 40 g kg–1 of RHs to broiler diets containing low levels of Ca (0.5%) and total P (0.3-0.5%) enhanced carcass weights. The increase in carcass weights was due to a reduction in gut weights and the addition of RHs, partly because of their physical structure, contributed more to this than phytase supplementation. Cellulase supplementation did not enhance phytase efficacy.